Advanced fetal MRI: Diffusion tensor imaging, spectroscopy, dynamic MRI, resting-state functional MRI - Soman, Salil; Kasprian, Gregor; Schopf, Veronika; Berger-Kulemann, Vanessa; Nemec, Ursula; Mitter, Christian; Prayer, Daniela (Journal of Pediatric Neuroradiology, 2012)
Fetal magnetic resonance imaging is playing an increasingly important role in troubleshooting diagnostically uncertain fetal ultrasound examinations. Recent advances in imaging speed and post processing of fetal images have enabled new applications of advanced neural imaging techniques to fetal imaging. This paper reviews recent developments in the topics of fetal diffusion tensor imaging, fetal spectroscopy, fetal dynamic imaging and resting state fetal magnetic resonance imaging.
Keywords: Fetal MRI; fetal diffusion tensor imaging; fetal spectroscopy; dynamic fetal MRI; resting state fetal MRI